The Impact Of The Organizational Climate On The Organization's Innovation Field Study In Sonelgaz Company-Unit Of DJELFA – (مجلة الواحات للبحوث والدراسات, 2022)
The current descriptive-analytic study aimed at identifying the effects of the organizational climate on the workers creativity at the Company of SONELGAZ-DJELFA's District  throughout        the          following  elements:(organizational structure, leadership, the style of communication, , technology and incentives) , at the significant level of (α≤0.05 ).A questioner of 38   questions containing all the elements of the organizational climate and movement's creativity was made.   The study was implemented on a sample of 32 elements.The study found that there is an impact of the organizational climate in its different dimensions on creativity in the institution under study.Keywords :organizational climate, innovation, organizational structure, leadership,  communication, technology, incentives